2012
DOI: 10.5424/sjar/2012101-105-11
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and seasonal trend of California red scale (Aonidiella aurantii Maskell) in citrus in Northern Spain

Abstract: The California red scale, Aonidiella aurantii (Maskell), was first detected in citrus groves in Catalonia, Northern Spain, in 2000, and has since spread slowly and irregularly. New foci of infestation are currently found in citrus-growing areas of southern Tarragona. As Catalonia is the northernmost citrus growing area in Spain, between 2002 and aurantii population dynamics and seasonal trends were studied in two citrus groves and compared with other regions and countries. The population dynamics showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The predation rate observed in the first A. aurantii generation could be explained by: (a) climatic conditions are optimal for most predator species in the study area at the end of the spring and beginning of the summer; (b) offspring of the first generation or overwintering generation of A. aurantii are usually the least abundant because they are the progeny of specimens that survived the winter; thus, there are less individuals to prey upon (Atkinson, ; Campos‐Rivela, Martínez‐Ferrer, & Fibla‐Queralt, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predation rate observed in the first A. aurantii generation could be explained by: (a) climatic conditions are optimal for most predator species in the study area at the end of the spring and beginning of the summer; (b) offspring of the first generation or overwintering generation of A. aurantii are usually the least abundant because they are the progeny of specimens that survived the winter; thus, there are less individuals to prey upon (Atkinson, ; Campos‐Rivela, Martínez‐Ferrer, & Fibla‐Queralt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stem‐tap sampling revealed a larger number of potential A. aurantii predators present in citrus agroecosystems. Nevertheless, some groups such as phytoseiid mites, dipterans, thrips as well as predator species with nocturnal activity that could also contribute to A. aurantii mortality (Campos‐Rivela et al., ; Sorribas & Garcia‐Marí, ; Vanaclocha et al., ) cannot be accurately sampled with this methodology, and we can therefore not determine the importance of these species.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, three factors must concur to achieve an optimal efficacy: (1) a maximum of sensitive instars, (2) a maximum of hatched eggs and (3) a minimum presence of new third instars. In Spain, almost every year, Aonidiella aurantii and other dispididae are chemically controlled with sprays in early June, during the maximum presence of sensitive instars of these scales (Campos-Rivela et al , 2012). At this time, the C. sinensis population is mostly composed of females, the most resistant stage, and thus these treatments are inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy allows natural enemy coexistence when depending upon the same prey resource (Hare et al, 1990;Vanaclocha et al, 2011). With the exclusion experiments, we studied the combined effect of the whole predator complex together which may have upon (Atkinson, 1977;Campos-Rivela et al, 2012); iii) as we observed in this study, predator seasonal-activity is highest during this generation (Lundgren, 2009;Hodek et al, 2012;Gómez-Marco et al, 2016 (Riechert & Lockley, 1984;Symondson et al, 2002) progressively increased their numbers throughout the growing season as had been previously observed (Monzó et al, 2014). In contrast to generalist and stenophagous predators, the specialist coccinellid predators of the family Diaspididae, R. lophanthae, C. bipustulatus and C. citricola, presented very low seasonal-activity and were mostly concentrated at the end of the season.…”
Section: Aonidiella Aurantii Mortality Attributed To Predation Was Nomentioning
confidence: 99%